Ectopic Cushing' syndrome caused by a neuroendocrine carcinoma of the mesentery - Fasshauer, Mathias (BioMed Central, 2006)
BACKGROUND: ACTH overproduction within the pituitary gland or ectopically leads to hypercortisolism. Here, we report the first case of Cushing' syndrome caused by an ectopic ACTH-secreting neuroendocrine carcinoma of the mesentery. Moreover, diagnostic procedures and pitfalls associated with ectopic ACTH-secreting tumors are demonstrated and discussed. CASE PRESENTATION: A 41 year-old man presented with clinical features and biochemical tests suggestive of ectopic Cushing's syndrome. First, subtotal thyroidectomy was performed without remission of hypercortisolism, because an octreotide scan showed increased activity in the left thyroid gland and an ultrasound revealed nodules in both thyroid lobes one of which was autonomous. In addition, the patient had a 3 mm hypoenhancing lesion of the neurohypophysis and a 1 cm large adrenal tumor. Surgical removal of the pituitary lesion within the posterior lobe did not improve hypercortisolism and we continued to treat the patient with metyrapone to block cortisol production. At 18-months follow-up from initial presentation, we detected an ACTH-producing neuroendocrine carcinoma of the mesentery by using a combination of octreotide scan, computed tomography scan, and positron emission tomography. Intraoperatively, use of a gamma probe after administration of radiolabeled (111)In-pentetreotide helped identify the mesenteric neuroendocrine tumor. After removal of this carcinoma, the patient improved clinically. Laboratory testing confirmed remission of hypercortisolism. An octreotide scan 7 months after surgery showed normal results. CONCLUSION: This case underscores the diagnostic challenge in identifying an ectopic ACTH-producing tumor and the pluripotency of cells, in this case of mesenteric cells that can start producing and secreting ACTH. It thereby helps elucidate the pathogenesis of neuroendocrine tumors. This case also suggests that patients with ectopic Cushing's syndrome and an octreotide scan positive in atypical locations may benefit from explorative radioguided surgery using (111)In-pentetreotide and a gamma probe.